2017
DOI: 10.3390/geosciences7020019
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Feasibility of a National InSAR Ground Deformation Map of Great Britain with Sentinel-1

Abstract: This work assesses the feasibility of national ground deformation monitoring of Great Britain using synthetic aperture radar (SAR) imagery acquired by Copernicus' Sentinel-1 constellation and interferometric SAR (InSAR) analyses. As of December 2016, the assessment reveals that, since May 2015, more than 250 interferometric wide (IW) swath products have been acquired on average every month by the constellation at regular revisit cycles for the entirety of Great Britain. A simulation of radar distortions (layov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 31 publications
0
44
0
Order By: Relevance
“…Looking at the applicability of satellite InSAR methods for geohazard mapping and monitoring, an approach to mapping a priori the feasibility of SAR imaging and InSAR monitoring of land deformation is presented by Novellino et al [1]. With a focus on the Sentinel-1 SAR constellation, the authors build upon the InSAR feasibility assessment developed in [13] for the ERS-1/2 and ENVISAT missions and run an analysis of Sentinel-1 data availability, topographic distortions, and land cover constraints toward the use of a novel SBAS algorithm to sense ground stability and motion across a whole country.…”
Section: Data Methods and Geohazard Domainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Looking at the applicability of satellite InSAR methods for geohazard mapping and monitoring, an approach to mapping a priori the feasibility of SAR imaging and InSAR monitoring of land deformation is presented by Novellino et al [1]. With a focus on the Sentinel-1 SAR constellation, the authors build upon the InSAR feasibility assessment developed in [13] for the ERS-1/2 and ENVISAT missions and run an analysis of Sentinel-1 data availability, topographic distortions, and land cover constraints toward the use of a novel SBAS algorithm to sense ground stability and motion across a whole country.…”
Section: Data Methods and Geohazard Domainsmentioning
confidence: 99%
“…In particular, three out of five of the latter citations were received by the first paper of the Special Issue that was published in March 2017 [1], and four out of five citations were made by papers published in other scientific journals in the field of remote sensing, EO, and Earth sciences.…”
Section: Statistics Bibliometrics and Impactmentioning
confidence: 99%
“…A pre-processing analysis showed that the possible geometrical distortion, relevant to have a more awareness in the investigation and interpretation of the products (Novellino et al, 2017), is low influence and the following track were chosen in order to capture as many as possible slope.…”
Section: Available Data and Methodologymentioning
confidence: 99%
“…Overall, the obtained results demonstrate that Ireland, even if geologically very stable, is still characterized by a dynamic and mutable landscape where gravity-driven or water-related ground movements are common at scales of between 10 −3 -10 1 km 2 and represent the main geo-hazards of the country. The success here of PS-InSAR with Sentinel-1 data in detecting such ground motions makes the technique a good candidate for upscaling such surveying to an island-wide SAR monitoring, as tested recently for neighboring Great Britain [67].…”
Section: Feasibility Of Sentinel-1 Ps-insar For Ground-motion Detectimentioning
confidence: 99%